Análise do impacto ambiental na produção de hidrogênio a partir da reforma a vapor convencional e com captura de CO2 - Yang, Lucas Hee Won (Universidade Federal de São Carlos, 2024)
Hydrogen is a promising energy source in the transition to a low-carbon economy, noted for its high efficiency and versatility. Its production from natural gas without CO2 capture accounts for approximately 62% of the hydrogen produced globally. Steam methane reforming is a widely used method for hydrogen production, however, it is also a significant source of CO₂ emissions, a greenhouse gas. The goals of the Paris Agreement aim to limit the global temperature increase to 1.5°C, which requires significant reductions in greenhouse gas emissions. Due to environmental concerns and to contribute to the targets set by the Paris Agreement, this study analyzes the impact of implementing carbon capture technologies on reducing CO₂ emissions associated with hydrogen production via steam methane reforming. Simulations of the processes were performed using specialized environmental assessment software (GREET), allowing for the quantification and comparison of emissions generated by both processes. The results indicate that CO₂ capture can substantially reduce CO₂ emissions, about a 95.73% reduction, decreasing the environmental impact of the steam methane reforming process and helping to achieve the target proposed by the Paris Agreement.
Analysis of the environmental impact of hydrogen production from conventional steam reforming and CO2 capture
Keywords: Hidrogênio; Reforma a vapor; Captura de carbono; Impacto ambiental; Emissões de CO₂; Hydrogen; Steam methane reforming; Carbon capture; Environmental impact; CO₂ emissions; ENGENHARIAS::ENGENHARIA QUIMICA